The effect of career development and transformational leadership on employee performance with employee engagement as a mediation variable in the general department of the regional secretariat of Malang city - Fitri Handayani; Dwi Orbaningsih; Umi Muawanah (Trigin Publisher, 2026)
The purpose of this study is to examine and analyze how career development affects employee engagement, how transformational leadership shapes employee engagement, how career development contributes to employee performance, how transformational leadership impacts employee performance, and how employee engagement relates to employee performance. Beyond these direct relationships, this study also investigates whether employee engagement serves as a mediating variable between career development and employee performance, as well as between transformational leadership and employee performance. A total of 141 employees were involved as research respondents, with SmartPLS employed as the primary tool for data analysis. The findings reveal that career development exerts a significant effect on employee engagement, while transformational leadership demonstrates a positive contribution toward employee engagement. Regarding performance outcomes, both career development and transformational leadership proved to have meaningful impacts on employee performance. Employee engagement likewise emerged as a significant determinant of employee performance. In addition, the results confirm that employee engagement functions as a mediating variable in the relationship between career development and employee performance, as well as in the relationship between transformational leadership and employee performance.